ANALISA GENETIK PISANG HIBRID DIPLOID BERDASARKAN MARKA RAPD (Random Amplified Polymorphic DNA) [Genetic Analysis of Diploid Banana Hybrids Based on RAPD Markers] - Martanti, Diyah; Poerba, Yuyu Suryasari; Herlina, Herlina (Research Center for Biology-Indonesian Institute of Sciences, 2017)
Banana breeding by crosses is one way to get new cultivars with a better quality. This study aims to verify molecular characteristic of diploid hibrid bananas i.e MDRK, SNMT and MDMT using Random Amplified Polymorphic DNA (RAPD) markers. Ten RAPD primers have been selected to detect the differences in molecular pattern from all three diploid hybrid bananas. The results showed that the hybrid combination of MDRK, SNMT and MDMT produced bands that shared some similarities with each parents by 43.83%, 51.25% and 47.21% respectively as the number of bands from type I, III and IV markers. Type III marker is the important marker for identification of male parents. Type VII marker (non-parent bands) was detected from hybrid MDRK, SNMT and MDMT by 18 (20.22%), 6 (7.5%) and 11 (12.64%) respectively. Marker of type VII can be used to identified hybrid because they are present only in offspring. The highest polymorphic bands was obtained by SNMT (83.9%) and the lowest obtained was performed by MDMT (71.25%). From this result, RAPD markers can be used as a tool to detect the differences of molecular pattern of diploid hybrid bananas.